2018
DOI: 10.21891/jeseh.432524
|View full text |Cite
|
Sign up to set email alerts
|

Improving Elementary School Teacher Candidates’ Views of Nature of Science Through Intensive Education

Abstract: Elementary school teacher candidates' (student teachers or STs) views of nature of science are important for an effective science teaching that aims to improve children's scientific literacy. The purpose of this study was to improve STs' views of nature of science through an intensive intervention. The study group consisted of 65 third year STs who were attending a major university in Ankara Turkey during the 2015-2016 fall semester. An educational program with a variety of activities that were designed to hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
1
3
0
2
Order By: Relevance
“…The results showed that teacher candidates' opinions for both items were compatible with the characteristics of the nature of science and their knowledge was scientifically sufficient. On the other hand, in another study, Ecevit, Yalaki and Kingir (2018) stated that only 33% of elementary school teacher candidates believed that scientific knowledge is experimental. Aydemir, Kazanç and Karakaya Cirit (2016) also found that 66.67% of science teachers and 78.95% of teacher candidates had a scientific perception that scientific knowledge is experimental based.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The results showed that teacher candidates' opinions for both items were compatible with the characteristics of the nature of science and their knowledge was scientifically sufficient. On the other hand, in another study, Ecevit, Yalaki and Kingir (2018) stated that only 33% of elementary school teacher candidates believed that scientific knowledge is experimental. Aydemir, Kazanç and Karakaya Cirit (2016) also found that 66.67% of science teachers and 78.95% of teacher candidates had a scientific perception that scientific knowledge is experimental based.…”
Section: Discussionmentioning
confidence: 95%
“…In this respect, it is important for teachers to have sciencerelated competencies in order for their students to learn the nature of science (İnce & Özgelen, 2017). On the other hand, teacher candidates' insufficient knowledge in the nature of science and misconceptions may be formed in their early education and those misconceptions have effects on shaping their opinions about the nature of science (Ecevit, Yalaki & Kingir, 2018). More specifically, teachers and teacher candidates' knowledge about the nature of science has critical importance in teaching science-related concepts (Dorsah, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Öğretmenlerin fen ve teknoloji arasındaki ilişki hakkındaki düşüncelerindeki değişime bakıldığında ise, teknolojik araştırmalara fendeki araştırmalardan daha çok para harcanmalı ve teknolojideki gelişmelerin bir çok kısmı fendeki keşiflerden meydan gelmiştir maddeleri ile ilgili olarak kurs öncesi kısmen doğru veya yanlış düşüncelere sahip olan 8 öğretmenin kurs sonrasında doğru düşünceye sahip olduğu görülmüştür (p< .05). Bu durumda HİE kurs etkisiyle sınıf öğretmenlerinin fen ve teknolojinin doğası ve birbirleri olan ilişkisi hakkındaki yanlış ve kısmen doğru düşüncelerinin doğru düşünceye dönüştüğü söylenebilir (Ecevit, Yalaki & Kingir, 2018).…”
Section: Journal Of Bayburt Educationunclassified
“…Не определены и не обоснованы единые условия интенсификации, доступные для понимания и применения широкой массой педагогического сообщества. Значительное количество научных исследований, посвященных интенсивному обучению, изучают интенсификацию отдельных аспектов учебного процесса (Комарова, 2015;Кондратьева, Валеев, 2017;Мухачева, 2010;Петрусинский, 1987;Рыбакова, 2015;Тасмуратова, 1997;Ecevit, Yalaki, Kingir, 2018).…”
Section: Introductionunclassified